Pengaruh Self-Esteem, Career Competencies Terhadap Career Adaptability Yang Dimoderasi Oleh Career Shock Pada Karyawan Bank Syariah Indonesia (BSI) Kota Banda Aceh - Rahmayani, Dewi; Usman, Muliati (Manajemen Inovasi Bisnis dan Strategi, 2024)
This research aims to determine the influence of Self-Esteem and Career Competencies on Career Adaptability which is moderated by Career Shock at the employee of Bank Syariah Indonesia, Banda Aceh. This research is quantitative research. Data collection for the study was done by using a questionnaire. The population in this study were all employees of Bank Syariah Indonesia (BSI) Banda Aceh City who came from conventional banks with a total of 111 people. The method used in this research is simple random sampling. The data analysis method used is Statistical Product For Social Science (SPSS) which is used as an analysis method to determine the influence between the variables studied. Based on the research results, it was found that Self-Esteem and Career Competencies have a significant direct effect on Career Adaptability. The finding of the study also shows that Career Shock has a significant effect on Career Adaptability. Then, it was also found that Career Shock moderated the influence of Self-Esteem on Career Adaptability. Besides, Career Shock moderated the influence of Career Competencies on Career Adaptability.Keywords: Self Esteem; Career Competencies; Career Adaptability; Career Shock